Does open access to academic research help small, science-based companies? - ElHassan ElSabry; Koichi Sumikura (Journal of Industry-University Collaboration, 2020)
Purpose – This study investigates the extent to which a company's usage of open access (OA) literature for R&D activities depends on its size. The authors’ assumption is that smaller pharmaceutical companies have less access to (usually expensive) journal subscriptions. Design/methodology/approach – A fixed-effect Poisson model was used to study a panel dataset of USPTO pharmaceutical company patents. The dependent variable is the count of citations to OA resources in a given company patent. Findings – Results support current anecdotal evidence that many SMEs suffer from high journal prices. Originality/value – This result justifies the assumption made by policymakers about the potentially positive impact OA mandates have on national innovation activity. It was also shown that collaborating with universities can be a potential coping mechanism for companies that struggle to gain access to the journals they need. In addition to the novelty of its findings, this study introduces a new way to study the impact of OA in nonacademic contexts.